Optimized Dispatching for Integrated Energy System With Wind Power - Zhang, Tao; Yan, Xing; Zhang, Renmin; Ye, Qingquan; Ma, Junhua (Frontiers in Energy Research, 2022)
The intermittency and unpredictability are the obstacles to absorb all wind power. The combined heat and power (CHP) system has been widely utilized as a heat and electricity source and the heating load limits the regulatory capacity of CHP to reduce curtailed wind power. This paper proposes an optimization model of integrated power and heating network system to fully utilize curtailed wind power. The thermal inertia in primary heating network, thermal comfort of end-users and electric boiler in secondary heating network are included in multiple scenarios to analyze different operation strategies. The simulation results show that considering heating network inertia and thermal comfort of end-users could reduce curtailed wind power ratio from 15% to 9%. Adding peak-shaving electric boiler on the user sides can increase the system electric load and reduce the curtailed wind power while reducing the heat output of the CHP unit during the peak and low periods of the heat load at night. Moreover, there is less than 1% of curtailed wind power ratio if the Peak-shaving capacity ratio is higher than 10%, which means the application recommendations of installed electric boiler capacity is obtained to increase enough flexibility of power and heating network system.